Smart world, smart rules? On the Legitimacy of Digital Systems of Social Rules - Orwat, Carsten; Hügle, Anika; König, René (AoIR Selected Papers of Internet Research, 2016)
The rapid realization of the “Internet of Everything” requires and causes that systems of social rules for interactions are implemented, administered and enforced by digital means. Although this phenomenon has been discussed since works on “lex informatica” and “code is law” the issues of legitimacy are rather selectively addressed and public discourse lacks differentiation in this regard. We argue that different social rule systems have, in principle, various requirements for legitimacy and, thus, their evaluation needs differentiation. The contribution has the aims (1) to introduce a more nuanced view on the rather under-researched issue of legitimacy of digital systems of social rules. Therefore, we discuss case studies of recent Internet developments and evaluate them with insights from theory of democracy. (2) The contribution suggests options for action and approaches to generate or ensure legitimacy for the considered case studies.